Pengaruh Ukuran Dewan Komisaris, Ukuran Dewan Direksi, Ukuran Perusahaan, Kepemilikan Institusional, Dan Komisaris Independen Terhadap Kinerja Keuangan - Novta Indra Haryani; Clara Susilawati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to determine the effect of board of commissioners size, board of directors size, company size, institutional ownership, and independent commissioners on financial performance. The research method used is multiple linear regression, the study population is a manufacturing company listed on the Indonesia Stock Exchange in 2019-2021, the sampling method used is purposive sampling and it is known that the research sample is 171. The results show that the size of the board of commissioners, the size of the board directors, company size, institutional ownership, and independent commissioners on financial performance have a positive and significant impact on financial performance. For future researchers who wish to conduct further research related to financial performance, it is better to use a longer entire period so that the results of this study will be better. Keyword : Board of Commissioners, Board of Directors, Company Size, Institutional Ownership, Independent Commissioner, Financial Performance.